(untitled) (Research, Society and Development, 2022)
Hip surgeries are among the most performed in orthopedics and one of the most common complications is residual pain. Residual pain is a chronic complication that does not depend on movement to be triggered, the most common treatment for it is with opioid drugs, such as tramadol, morphine and oxycodone, but these drugs have a high potential to cause dependence and can trigger many side effects, such as drowsiness, constipation, nausea, vomiting and even lowering of the level of consciousness and consequent respiratory arrest. The objective is to analyze the epidemiological profile of cases of residual pain in patients in the late postoperative period of orthopedic surgeries in the hip joint according to the drug treatment used. The study presents as a qualitative and exploratory study, in which the evaluation of postsurgical medical records that present the therapy performed, its results and its complications will be conducted. It was observed in the studied records that more than 80% of the patients used opioid analgesics, most had good analgesic control, but opioid therapies were the ones with the most side effects. When therapies were associated with dipyrone, a high ratio between effectiveness and side effects was observed.